Bioinformatic analysis of a novel Echinococcus granulosus nuclear receptor with two DNA binding domains - Alvite, Gabriela (2019)
Nuclear receptors are ligand-activated transcription factors capable of regulating the expression of complex gene networks. The family includes seven subfamilies of proteins with a wide phylogenetic distribution. A novel subfamily with two DNA-binding domains (2DBDs) has been reported in Schistosoma mansoni (Platyhelminth, Trematoda). This work describes the cDNA cloning and bioinformatics analysis of Eg2DBDα, a 2DBD nuclear receptor isoform from the parasite Echinococcus granulosus (Platyhelminth, Cestoda). The Eg2DBDα gene coding domain structure was analysed. Although two additional 2DBD nuclear receptors are reported in the parasite database GeneDB, they are unlikely to be expressed in the larval stage. Phylogenetic relationships between these atypical proteins from different cestodes are also analysed including S. mansoni 2DBD nuclear receptors. The presence of two DNA binding domains confers particular interest to these nuclear receptors, not only concerning their function but to the development of new antihelminthic drugs.